In situ x-ray computed tomography of zinc–air primary cells during discharge: correlating discharge rate to anode morphology. (17th December 2021) - Hack, Jennifer; Patel, Drasti; Bailey, Josh J; Iacoviello, Francesco; Shearing, Paul R; Brett, Dan J L
Abstract: Zinc–air batteries have gained significant attention as safe battery alternatives, with high theoretical energy densities and a high abundance of their constituent materials. However, barriers to their widespread adoption include the need to improve their cycling lifetime, as well as stability and avoiding degradation mechanisms such as zinc dendrite growth and hydrogen-producing side reactions. X-ray computed tomography (CT) is a widely used technique for the study of batteries. In situ / operando x-ray CT has been increasingly used to study the zinc anode of zinc–air batteries to evaluate the interesting morphological changes occurring during the reaction from zinc (Zn) to zinc oxide (ZnO) during discharge (vice versa during charge). However, several studies have been carried out using synchrotron x-ray sources, which have limited availability for users. In this work, we present a comprehensive study of the discharge of commercial, primary zinc–air batteries using a laboratory-based x-ray source for in situ x-ray CT measurements. Four different discharge rates are investigated ( C /30, C /60, C /90 and C /150), with tomograms collected at various stages throughout each discharge. Results confirm that with decreasing C -rate (i.e. decreasing discharge current) a greater volume of zinc is reacted, with average mass utilisations of 17%, 76%, 81% and 87% for C /30, C /60, C /90 and C /150, respectively. Furthermore, quantification using x-ray CT datasets showed that there is a direct correlation between the volume of zinc remaining in the cell and the state-of-charge of the cell, which deviated from linearity for the longer C -rates. Finally, a potential new mechanism for shape change is discussed, where a Zn particle is replaced with a pore of a similar volume. As well as improvements in statistical relevance gained from multiple repeats for each C- rate, the results presented here could be used in both modelling of battery performance, as well as consideration for future anode design concepts.